Multi jet fusion printing of an integrated strain and humidity sensor - Muhammad Muhsin Bin Aziz (Nanyang Technological University, 2023)
In the field of wearable technology, the demand in flexible sensing devices is driven by the healthcare monitoring field as it has the potential to eliminate the need of complex machines to monitor physiological parameters of patients. A sensor embedded in a flexible polymer matrix form an important component in the wearable devices. Studies have been conducted in using 3D printing to fabricate strain and humidity sensors with various materials. However, not much exploration has been conducted in using Multi Jet Fusion (MJF) 3D printing system to fabricate an integrated strain and humidity sensor. MJF inkjet technology allows the fabrication of materials on a site-specific basis and different concentrations over multiple regions. The inkjet system in the MJF 3D printer forms the main motivation of this project. In this project, graphite nanoplatelets (GNPs) and carbon nanotubes (CNTs) were used to form a conductive agent as part of an integrated strain and humidity sensor design for the MJF inkjet system. Thermoplastic urethane (TPU) was used as the flexible matrix of the sensor design and fused with the conductive agent that was prepared and loaded into the inkjet cartridge to fabricate an integrated strain and humidity sensor. Characterization was conducted on the fabricated sensor. Its potential to detect strain, human motion and humidity was analyzed. The fabricated sensor was subjected to cyclic stretch and compression cycles in various directions as part of strain analysis. For motion analysis, the sensor was attached to back of a human leg to detect resistance change in the sensor. To detect humidity, the sensor was placed in a human mask and its electrical conductivity and resistance change was analyzed. The potential of the fabricated sensor to be integrated with another sensor was also discussed.